DAMPAK PERUBAHAN IMBAL HASIL OBLIGASI AMERIKA SERIKAT TERHADAP INDEKS HARGA SAHAM GABUNGAN INDONESIA - Aji, Dwi Cahyono; Abdullah, Mohammad Faisal (Journal of Financial Economics & Investment, 2023)
This study aims to determine the effect of external macroeconomic factors represented by US bond yields, the rupiah exchange rate against the US dollar, and the Standard and Poor's 500 (S&P 500 index) on the Jakarta Composite Stock Price Index with monthly data. The analysis technique used in this study is multiple linear regression analysis. Then do the T test to test the partial effect of the independent variables, F test to test the simultaneous effect of the independent variables and test the coefficient of determination. To find out the feasibility of the research model, a classical assumption test was also carried out. The results of the study are that all independent variables have an overall significant effect on the Jakarta composite index. While partially the United States bond yield variable and the S&P 500 index have a positive and significant effect on the JCI. On the other hand, the rupiah exchange rate variable against the US dollar has a negative and significant effect on the Jakarta Composite Stock Price Index.